2022
DOI: 10.3389/fpls.2022.844450
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Genetic Basis of Key Agronomic Traits of Wrinkled Vining Pea (Pisum sativum L.) for Sustainable Production

Abstract: Estimating the allelic variation and exploring the genetic basis of quantitatively inherited complex traits are the two foremost breeding scenarios for sustainable crop production. The current study utilized 188 wrinkled vining pea genotypes comprising historical varieties and breeding lines to evaluate the existing genetic diversity and to detect molecular markers associated with traits relevant to vining pea production, such as wrinkled vining pea yield (YTM100), plant height (PH), earliness (ERL), adult pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 79 publications
(96 reference statements)
0
4
1
Order By: Relevance
“…The observed LD decay was much faster than that reported by Alemu et al (2022) for a collection of 188 vining pea varieties and breeding lines provided by a single company (where r 2 = 0.2 was reached at 6,930,000 bp on average vs. 1,445 bp in our study), while being slower compared to what reported by Pavan et al (2022) for a larger germplasm collection (where r 2 = 0.2 was reached at 30 bp on average). These results are in substantial accordance with expectations, considering that the first genetic base was likely much narrower, while the second one was more diversified, relative to the current one.…”
Section: Trait Acontrasting
confidence: 48%
“…The observed LD decay was much faster than that reported by Alemu et al (2022) for a collection of 188 vining pea varieties and breeding lines provided by a single company (where r 2 = 0.2 was reached at 6,930,000 bp on average vs. 1,445 bp in our study), while being slower compared to what reported by Pavan et al (2022) for a larger germplasm collection (where r 2 = 0.2 was reached at 30 bp on average). These results are in substantial accordance with expectations, considering that the first genetic base was likely much narrower, while the second one was more diversified, relative to the current one.…”
Section: Trait Acontrasting
confidence: 48%
“…[405][406][407] It has been a model plant in genetics since the 18th century. 408 From peas, a high protein content can be extracted with potential for application as a food ingredient, and this statement is corroborated by the results obtained in the work of Arteaga et al 409 In addition, peas are also an important source of starch, which can be extracted from their two seed phenotypes: the "smooth" and "wrinkled" type. 410,411 From the pea it is possible to extract approximately 45.9% 412 and 85.97% 413 of starch, which is the most abundant carbohydrate.…”
Section: Pla/pea Starchmentioning
confidence: 63%
“…Several reports on different crops including legumes have shown the potential of using DArTseq to determine population structures and associating genetic markers with different traits ( Akbari et al., 2006 ; Raman et al., 2014 ; Aznar-Fernández et al., 2020 ; Alemu et al., 2022 ). By using DArTseq in this population we could identify 6,606 SNP markers evenly distributed in the faba bean genome, and 51 of those markers were identified to be associated with ten of the characterized traits through our GWAS.…”
Section: Discussionmentioning
confidence: 99%